Association of sugary beverages consumption with liver fat content and fibro-inflammation: a large cohort study - Zhou, Yiheng; Jia, Yu; Yao, Yi; Cheng, Yu; Cheng, Yonglang; Yang, Rong; Zeng, Rui; Wan, Zhi; Zhao, Qian; Li, Dongze; Lei, Yi; Liao, Xiaoyang (Frontiers in Public Health, 2025)
ObjectiveLiver fat content (LFC) and hepatic fibro-inflammation (HFI) accumulation are the primary pathological manifestation of steatohepatitis. The association between intake of sugary beverages (SBs), including artificially-sweetened beverages (ASB), sugar-sweetened beverages (SSB), and natural juices (NJs), and LFC or HFI remains unclear.MethodsThe study included 25,885 participant who completed at least one online dietary assessment and magnetic resonance imaging. LFC and HFI were quantified using the liver proton density fat fraction (PDFF) and iron-corrected T1 (cT1).ResultsCompared to those without ASB and SSB intake, the arithmetic mean difference (AMD) of PDFF was 0.15 (95% Cl: 0.06 to 0.24) and 0.21 (95% Cl, 0.12 to 0.29), and the AMD of cT1 was 3.86 (95% CI, 1.26 to 6.79) and 2.43 (95% CI, 1.31 to 3.57) in individuals with ≥1 serving/d, respectively. Individuals with 0–1 serving/d had lower PDFF (AMD: −0.10 95%Cl: −0.19 to −0.01) than those without NJs intake. In Quantile G-computation models, SSB and ASB contributed most in the AMD of PDFF (54.7%) and cT1 (53.1%), respectively. When replacing ASB and SSB with water, the progress of PDFF was improved.ConclusionArtificially-sweetened beverages and SSB intake were positively associated with LFC and HFI, and moderate NJs intake was slightly negatively associated with LFC but not HFI.